Hot coal, cold steel : Russian and Ukrainian workers from the end of the Soviet Union to the post-communist transformations - Crowley, Stephen, 1960- (University of Michigan Press, 1997)
In a comparative study of coal miners and steelworkers at the end of the Soviet era, Stephen Crowley sheds light on where these industrial workers have been and where they are going. Coal miners in the final years of the Soviet Union organized and led strikes that supported the end of Communism, even though their heavy subsidies would be threatened by capitalism. Steelworkers, in contrast, did not effectively organize and strike. This pattern has continued under the new governments, with the coal miners well organized and seeking protection from the worst consequences of marketization, while the steelworkers unions remain weak despite deteriorating economic conditions.